A new approach to β-decays studies impacting nuclear physics and astrophysics: The PANDORA setup - Mascali D.; Santonocito D.; Busso M.; Celona L.; Galatà A.; La Cognata M.; Mauro G. S.; Mengoni A.; Naselli E.; Odorici F.; Palmerini S.; Pidatella A.; et al. (EPJ Web of Conferences, 2023)
Theory predicts that lifetimes of β-radionuclides can change dramatically as a function of their ionization state. Experiments performed in Storage Rings on highly ionized atom have proven nuclei can change their beta decay lifetime up to several orders of magnitude. The PANDORA (Plasmas for Astrophysics, Nuclear Decay Observation and Radiation for Archaeometry) experiment is now conceived to measure, for the first time, nuclear β-decay rates using magnetized laboratory plasma that can mimic selected stellar-like conditions in terms of the temperature of the environment. The main feature of the setup which is based on a plasma trap to create and sustain the plasma, a detector array for the measurement of the gamma-rays emitted by the daughter nuclei after the decay process and the diagnostic tools developed to online monitor the plasma will be presented. A short list of the physics cases we plan to investigate together with an evaluation of their feasibility will be also discussed.